2023
DOI: 10.1039/d3nr01112g
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and phosphorus co-doping optimized electronic structure and modulated intermediate affinity on PdSP metallene for ethanol-assisted energy-saving H2production

Abstract: Coupling cathodic hydrogen evolution reaction (HER) and anodic electrochemical oxidation of organic small molecules in a co-electrolysis system could simultaneously realize high value chemicals generation and energy-saving hydrogen production, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…48,49 Recently, Wang and coworkers synthesized a S and P dual-doped Pd metallene (PdSP metallene). 34 In such a PdSP metallene system, the co-incorporation of S and P atoms endows the resultant PdSP metallene with abundant active sites and significantly increases the electrochemically active area. Moreover, the electronic interaction between Pd and nonmetals can also optimize the electronic structure of active sites and modify the intermediates’ affinity toward the active sites.…”
Section: Strategies For Modifying Metallenesmentioning
confidence: 99%
See 2 more Smart Citations
“…48,49 Recently, Wang and coworkers synthesized a S and P dual-doped Pd metallene (PdSP metallene). 34 In such a PdSP metallene system, the co-incorporation of S and P atoms endows the resultant PdSP metallene with abundant active sites and significantly increases the electrochemically active area. Moreover, the electronic interaction between Pd and nonmetals can also optimize the electronic structure of active sites and modify the intermediates’ affinity toward the active sites.…”
Section: Strategies For Modifying Metallenesmentioning
confidence: 99%
“…Moreover, some effective strategies are also proposed to improve their electrocatalytic performance, including alloying, atomic doping, nonmetal doping, strain engineering, defect engineering, surface functionalization, and heterostructure engineering. 29–34…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well known, Pd-based nanomaterials are reported to be advanced electrocatalysts for electrocatalytic AOR due to their intrinsically high electrocatalytic activity. 48–51 In recent years, modifying the electronic structure of Pd has paved another pathway for substantially enhancing their electrocatalytic performance. 52–60 Incorporating H atoms into Pd lattice can tailor the d-band center of Pd and accelerate the reaction kinetics by weakening the bond between the catalyst and reaction intermediate.…”
Section: Applications Of H Intercalated Pd-based Nanocatalysts For El...mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Moreover, compared with the energy-intensive and kinetically sluggish oxygen evolution reaction (OER), the alcohol oxidation reaction (AOR) can largely reduce the energy input. 17,18 Previous reports have demonstrated that catalysts containing transition metal elements such as Ni, Co, Cu, Fe, etc. are potential alternative catalysts for the electrooxidation of alcohols due to the inherent electronegativity of the elements.…”
Section: Introductionmentioning
confidence: 99%